جنس میں تبدیلی اور اس کے فسخِ نکاح پر اثرات: Gender Change and its Impact on Nikah - Abdul Hameed; Hannan, Abdul (Al Basirah, 2023)
This research paper examines the complex issue of gender change and its implications on Nikah, the Islamic marriage contract. By analyzing Islamic legal sources, scholarly opinions, and contemporary discussions, the study explores the challenges and considerations arising from individuals undergoing gender transition and their desire to enter into or maintain a Nikah. The research examines different schools of thought within Islamic jurisprudence and their varying interpretations on the permissibility and validity of marriages involving individuals who have undergone gender reassignment. It delves into the fundamental principles of Nikah, such as the importance of consent, compatibility, and the preservation of legal rights and responsibilities. Furthermore, the paper explores the ethical and social dimensions surrounding gender transition within an Islamic framework, addressing questions related to identity, biological sex, and the concept of "gender at birth." The study also investigates the perspectives and experiences of Muslim communities and religious authorities on this matter, considering the need for compassion, inclusivity, and the protection of individual rights. Additionally, the paper examines the potential legal and societal implications of recognizing gender change within the context of Nikah, including inheritance rights, family law, and the overall functioning of Islamic marital institutions. The findings of this research shed light on the complexities surrounding gender change and its impact on Nikah, providing a comprehensive understanding of the diverse perspectives within Islamic discourse. The research contributes to the ongoing discussions on gender, identity, and marriage in contemporary Muslim societies, emphasizing the need for compassionate and informed approaches to address the unique challenges posed by gender transition within an Islamic legal and ethical framework.